Efficacy of Leuprolide Acetate 1-Month Depot for Central Precocious Puberty (CPP): Growth Outcomes During a Prospective, Longitudinal Study - Lee, Peter A (BioMed Central, 2011)
INTRODUCTION: Gonadotropin-releasing hormone analogs (GnRHa) are the treatment of choice for CPP. We investigated growth in GnRHa-naïve subjects, treated with leuprolide acetate 1-month depot for CPP. METHODS: This prospective, open-label study had a long-term, observational, follow-up period. Forty-nine females and 6 males were enrolled. Leuprolide acetate depot was administered intramuscularly every 28 days. Height and growth rate during and after treatment until adulthood were measured. RESULTS: Among 30 of 49 females having an adult height (AH) measurement, 29 had target heights available (mean = 163.8 cm) and 27 had pretreatment predicted adult heights (PAHs; mean = 157.4 cm). After treatment, the mean AH at mean age 21.8 years [range 13.7-26.7 years] was 162.5 cm, a mean height gain over baseline PAH of 4.0 cm. The mean height standard deviation score was -0.1 at AH. CONCLUSIONS: Treatment of CPP with leuprolide acetate 1-month depot had beneficial effects on growth rate and preservation of AH. TRIAL REGISTRATION: ClinicalTrials.gov: NCT00660010